Impact of Infancy Conditions on Physical Growth of Children Under-five - Azhari, Claudia; Mahwati, Yeni; Suryamah, Yeni; Ramdan, Arfian Hikmat (citeus, 2024)
Children under five years old is the age group most vulnerable to several health problems. It is important to evaluate the impact of infancy condition on their physical growth. This research aimed to examine the impact of infancy condition on the physical growth of children under-five years old. The unmatched case-control study was conducted in Puskesmas Griya Antapani areas, Bandung from May to July, 2023. A total of 112 children aged under 5 years were included in this study (56 cases and 56 control). The analysis used multivariate logistic regression to determine adjusted odds ratios (OR). The results showed that the variables associated with the children growth are infection or illness in infancy (OR is 0,138 95 percent CI 0,51 until 0,375), feeding patterns in infancy (OR is 11,000 95 percent CI 4,566 until 26,503), birth weight (OR is 0,170 95 percent CI 0,036 until 0,818) and economic status (OR is 0,062 95 percent CI 0,14 until 0,280). Multivariate logistic regression showed that economic status was the most dominant factor for children physical growth (OR is 6.701 95 percent CI 1,323 until 33,944). Education for families is needed in choosing food that is rich in nutrition and economical by utilizing alternative sources of protein, the amount of food, and the schedule of meals according to the needs of children according to their age.